The tenth circle - Picoult, Jodi (New York : Atria Books, 2006)
When the daughter of a comic book artist claims she has been raped at a party and her friends turn against her, she runs away to Alaska and her father must face his own violent past as he tries to find her.
National College of Business and Arts
Keywords: Date rape -- Fiction; Psychological fiction